[Bus Crossing Metal Bridge] - Streng, Evelyn Fiedler (1975)
Photograph of a bus crossing a metal bridge. The light blue and white bus sits at the end of an elevated. rusted bridge crossing a grey stone canyon. Boulders sit along the edge of the canyon and across black dirt. A person in a white sweater beckons the bus to continue moving on the bridge.